Adolescent female rats undergo full systems consolidation of an aversive memory, while males of the same age fail to discriminate contexts - Crestani, Ana P.; Lotz, Fernanda N.; Casagrande, Mirelle A.; Popik, Bruno; Guerra, Kétlyn T. K.; de Oliveira Alvares, Lucas; Quillfeldt, Jorge A. (bioRxiv, 2021)
Generalization is an adaptive process that allows animals to deal with threatening circumstances similar to prior experiences. Systems consolidation is a time-dependent process in which memory loses it precision concomitantly with reorganizational changes in the brain structures that support memory retrieval. In this, memory becomes progressively independent from the hippocampus and more reliant on cortical structures. Generalization, however, may take place much faster in adult animals depending on the presence of sex hormones. Notwithstanding its relevance, there are few studies on sex differences in memory modulation. Here, a contextual fear discrimination task was used to investigate the onset of memory generalization and hippocampus-independence in adolescent male and female rats (P42-49). Subjects were tested 2, 7, 14, 21 or 28 days after training, with females showing memory generalization from day 21 on, whereas males surprisingly unable to discriminate contexts at any time. Ovariectomized females, however, displayed an early onset of generalization. Consistently, pre-test pharmacological blocking of dorsal hippocampus was able to impair memory retrieval in females, but not in males, which indicate that precise memory is dependent on the hippocampus. To our notice, this is the first report of a memory systems consolidation process – expressed in its two dimensions, neuroanatomical and qualitative – in adolescent female rats, and one that can also be accelerated by the reduction of sex hormones through ovariectomy. It is also unprecedented that despite adolescent male rats being able to remember fear learning, they did not discriminate contexts with any precision.